State-of-the-art and perspectives of cutting edge preparation and its effect on the cutting performance of titanium alloy - Pan, Fangwei; Yuan, Haiyang (Frontiers in Materials, 2023)
Titanium alloys are commonly used in industrial applications due to their exceptional mechanical and chemical properties. However, their low thermal conductivity and high chemical reactivity pose significant challenges in machining, leading to increased cutting forces, rapid tool wear, and poor surface quality. To overcome these issues, advanced cutting edge preparation techniques have been developed to enhance the machining performance of titanium alloys. This paper provides an overview of state-of-the-art cutting edge preparation techniques for titanium alloy machining and examines their effects on machining performance. It first presents a characterization method for cutting edge geometry and explores how it affects machining performance, demonstrating that strategic cutting edge preparation can significantly enhance performance by reducing cutting forces and improving surface finish. The paper also emphasizes the underlying mechanisms of cutting edge preparation and its impact on machining performance and subsequent cutting edge erosion. Finally, it concludes by discussing future research directions in this field, highlighting the need to develop new cutting edge preparation techniques and optimize existing ones. Overall, this paper serves as a valuable resource for researchers and engineers seeking to improve the cutting performance of titanium alloys in various applications.